180k views
3 votes
Find the equivalent expression of 3^-2

Find the equivalent expression of 3^-2-example-1
User DrHaze
by
5.7k points

1 Answer

2 votes

\bf a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------\\\\ \cfrac{3^2}{3^4}\implies 3^2\cdot 3^(-4)\implies 3^(2-4)\implies 3^(-2)\quad \checkmark \\\\\\ \cfrac{3^1}{3^3}\implies 3^1\cdot 3^(-3)\implies 3^(1-3)\implies 3^(-2)\quad \checkmark
User JoeButler
by
5.8k points